Numerical Linear Algebra
This comprehensive text provides a thorough understanding of the fundamental theories and algorithms of numerical linear algebra. Putting emphasis on the implementation of MATLAB software for problem-solving, the text explains the application of various algorithms for the essential topics of the subject including elimination and iterative methods, condition number of a matrix, eigenvalue problem and Householder and Givens matrices. The book is primarily designed for postgraduate students of Mathematics.